Kerusakan Usus pada Mencit (Mus musculus) yang Diinokulasi Larva 3 (L3) Anisakis spp. - Febrina Dian Permatasari; Poedji Hastutiek; Lucia Tri Suwanti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
This study aims to be show damage in the intestine of mice caused by inoculation of the larvae of Anisakis spp. alive and who has died because of a warming 750C for 7 minutes. Eighteen male mice (Mus musculus) were divided into three groups: control group, a group of mice were inoculated the larvae of Anisakis spp. alive andgroups of mice were inoculated the larvae of Anisakis spp. who have died. 48 hours post inoculation, the mice’s intestines necropsy performed later performed HE staining to identify and scoring intestinal histopathology. The results showed inoculation of the larvae of Anisakis spp. either alive or dead induce histological changes in the intestine in the form of infiltration of inflammatory cells, epithelial changes and structural changes in the intestinal mucosa